Demethylating therapy increases anti-CD123 CAR T cell cytotoxicity against acute myeloid leukemia - Nadia El Khawanky (Nature Portfolio, 2021)
The success of CAR-T cells for treating acute myeloid leukaemia (AML) is hampered by toxicity to normal cells and low CAR-T cell persistence. Here, the authors show that the demethylating compound 5′-Azacitdine increases anti-CD123 CAR-T cell cytotoxicity against AML.